2021
DOI: 10.1186/s13102-021-00333-w
|View full text |Cite
|
Sign up to set email alerts
|

The interaction effect of aerobic exercise and vitamin D supplementation on inflammatory factors, anti-inflammatory proteins, and lung function in male smokers: a randomized controlled trial

Abstract: Background This study aimed to investigate the interaction effect of aerobic exercise and vitamin D supplementation on inflammation (TNF-α, IL-6, CC16, SP-D, and CC16/SP-D ratio) and lung function (FEV1, FVC, and FEV1/FVC ratio) in male smokers. Methods After applying inclusion criteria, a total of 40 healthy male smokers were recruited in this study. The participants were randomly divided into four groups as follows: Aerobic Exercise + vitamin D … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
24
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(26 citation statements)
references
References 37 publications
1
24
0
Order By: Relevance
“…Inclusion criteria are as follows: (1) The patients met the diagnostic criteria for medium and advanced lung cancer in Chinese Medical Association Guidelines for Clinical Diagnosis and Treatment of Lung Cancer (2018 edition) [ 11 ] and were diagnosed as lung cancer by pathological and imaging examination. (2) The patients possessed cognitive and communication ability.…”
Section: Methodsmentioning
confidence: 99%
“…Inclusion criteria are as follows: (1) The patients met the diagnostic criteria for medium and advanced lung cancer in Chinese Medical Association Guidelines for Clinical Diagnosis and Treatment of Lung Cancer (2018 edition) [ 11 ] and were diagnosed as lung cancer by pathological and imaging examination. (2) The patients possessed cognitive and communication ability.…”
Section: Methodsmentioning
confidence: 99%
“…A previous study found that combining aerobic exercise with vitamin D3 supplementation can upregulate the levels of serum CC16 in patients with lung injury caused by smoking ( 71 ). However, the specific mechanism was not elucidated ( 71 ).…”
Section: Discussionmentioning
confidence: 99%
“…A previous study found that combining aerobic exercise with vitamin D3 supplementation can upregulate the levels of serum CC16 in patients with lung injury caused by smoking ( 71 ). However, the specific mechanism was not elucidated ( 71 ). Compared with the findings reported by Mathyssen et al ( 26 ), this previous study found no clear association between vitamin D3 supplementation and the degree of EMT of bronchial epithelial cells ( 71 ).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…It is thought that AT, as a mechanical stimulus, may play a key role in modifying endothelial activity and the expression of a variety of proteins, particularly those involved in local inflammation (e.g., Interleukin-6 (IL-6), Interleukin-10 (IL-10), Cluster of Differentiation 27 (CD27), Chemokine (C-X-C motif) Ligand 13 (CXCL13). Studies investigating the effects of AT on inflammation in T2DM models are inconsistent [ 5 , 6 ] and limited to serum level analyses [ 7 , 8 ] or animal studies [ 9 , 10 ].…”
Section: Introductionmentioning
confidence: 99%